Bioactive Compounds and Anticancer Activities of Moringa Oleifera of East Nusa Tenggara Origin - Marylin Susanti Junias; I GustiNgurah Budiana; Apris A. Adu; R. Pasifikus Christa Wijaya; Indra Yohanes Kiling (Indian Journal of Forensic Medicine & Toxicology, 2021)
This research aimsto know the bioactive compound content of Moringa leaves and seeds so that later it can be developed as a candidate for anticancer drugs. The extraction process results showed n-hexane, ethyl acetate, and ethanol extract levels in the Moringa leaves, respectively; 11.38%; 25.56%, and 40.1%. TheLC50valuesoftheethylacetateextractofMoringaleavesandseedswere127.95 ppm and 117.52 ppm. Furthermore, the LC 50 values of the ethanol extract of Moringa leaves and seeds were 34.58 and 60.69 ppm. The levels of bioactive compounds of the ethyl acetate extract of Moringa leaves and seeds were 137.5 ppm and 6.5 ppm. Based on the anticancer activity test results, all extracts of both Moringa leaves and seeds have potent anticancer activity (<1000 ppm). The n-hexane extract and the ethanol extract of Moringa leave from Kupangcan be developed as ananticancer.